Investigating the Demographic Characteristics, Clinical Signs, Radiological and Laboratory Findings in Pregnant Women with COVID-19: A Cross-Sectional Study in Southern Iran - Parisa Sabetsarvestani; Soheila Rahnavard; Mahmood Hatami; Mostafa Bijani; Leila Nikrooz (Hamadan University of Medical Sciences, 2021)
Background and Objective: Pregnant women are one of the vulnerable groups against COVID-19. Understanding the affected population characteristics helps to identify risk factors and set more effective treatment goals; in this regard, the present study tries to review demographic characteristics, clinical signs, radiological and laboratory findings in pregnant women with COVID-19 in southern Iran. Material and Methods: This descriptive cross-sectional study was conducted on 30 pregnant women with COVID-19 who were selected from teaching hospitals in Fasa, Jahrom, and Shiraz in Fars province. Sampling was done through the convenience method from March to July 2020. A researcher-made checklist was applied to gather the required data which were analyzed using SPSS 22 software and descriptive statistics. Results: The mean age of patients was 28.30±9.96 years. Of patients, 60% were in the first trimester of pregnancy. The average length of stay in a hospital was 8.47±4.37 days. Fever (46/66 %) was the most common clinical finding, increased C-reactive protein (CRP) levels (50%) was the most common laboratory finding, and Ground Glossy Opacity (GGO) (56/66 %) was the most common radiological finding in both lungs. Of pregnant women, 80% with COVID-19 had an underlying disease. The most common underlying diseases were 36.66% for asthma and 20% for diabetes. Of normal deliveries, 53.33% and 3.33% of neonatal and maternal deaths were reported. Conclusion: The most common time for COVID-19 in pregnant women was reported in the first trimester of pregnancy with clinical signs of fever and a history of asthma and diabetes. Therefore, the findings of this study highlight the importance of paying attention to pregnant women as one of the most at-risk groups in the COVID-19 pandemic. Health policy makers can use the findings of this study and the reported outcomes to develop appropriate health protocols for health care of pregnant women in the COVID-19 pandemic.